A Systematic Review and Meta-analysis of Mobile Health Applications and Telemonitoring in Atopic Dermatitis Self-Management - Ivan Cherrez-Ojeda; Karla Robles-Velasco; María F. Osorio; Ana Ormaza Vera; Zouina Sarfraz; Azza Sarfraz; Annia Cherrez; Sofia Cherrez; Jorge Mario Sanchez Caraballo (Adis, Springer Healthcare, 2024)
Abstract Introduction Up to 25% of children and 5.6% of adults in the USA have atopic dermatitis (AD), with substantial impacts on quality of life. Effective control can be challenging despite therapy efforts. The emergence of information and communication technologies (ICT) in AD management prompted this study to assess its impact on self-management. We conducted a meta-analysis to assess outcomes from peer-reviewed clinical trials evaluating the effectiveness of teledermatology, mobile health (mHealth) apps, and electronic devices for managing AD. Methods We searched PubMed, Web of Science, Scopus, and Embase for articles written in English and published until May 2023. Results Twelve trials with 2424 participants were selected from 811 studies. A meta-analysis of 1038 individuals reported a mean difference (MD) of −1.57 [95% confidence interval (CI): −2.24, −0.91] for the Patient Oriented Eczema Measure (POEM). A meta-analysis of 495 individuals reported a Dermatology Life Quality Index (DLQI) MD of −0.59 [95% CI: −0.95, −0.23]. Despite heterogeneity (I 2 = 47% and I 2 = 74%), the impact was significant (P ≤ 0.001). SCORing Atopic Dermatitis (SCORAD) showed an insignificant MD of −0.12 (P = 0.91). Conclusion mHealth applications and telemonitoring show significant improvement in patients' quality of life (DLQI) and self-management (POEM) but no significant impact on AD severity (SCORAD).